Mosquito Host Seeking in 3D Using a Versatile Climate-Controlled Wind Tunnel System - Hinze, Annika; Lantz, Jörgen; Hill, Sharon R.; Ignell, Rickard (Frontiers in Behavioral Neuroscience, 2021)
Future anthropogenic climate change is predicted to impact sensory-driven behaviours. Building on recent improvements in computational power and tracking technology, we have developed a versatile climate-controlled wind tunnel system, in which to study the effect of climate parameters, including temperature, precipitation, and elevated greenhouse gas levels, on odour-mediated behaviours in insects. To establish a baseline for future studies, we here analysed the host-seeking behaviour of the major malaria vector mosquito, Anopheles gambiae sensu strico, to human odour and carbon dioxide (CO2), under tightly controlled climatic conditions, and isolated from potential background contamination by the presence of an experimenter. When presented with a combination of human foot odour and CO2 (case study I), mosquitoes engaged in faster crosswind flight, spent more time in the filamentous odour plume and targeted the odour source more successfully. In contrast, female An. gambiae s. s. presented with different concentrations of CO2 alone, did not display host-seeking behaviour (case study II). These observations support previous findings on the role of human host-associated cues in host seeking and confirm the role of CO2 as a synergist, but not a host-seeking cue on its own. Future studies are aimed at investigating the effect of climate change on odour-mediated behaviour in mosquitoes and other insects. Moreover, the system will be used to investigate detection and processing of olfactory information in various behavioural contexts, by providing a fine-scale analysis of flight behaviour.